1999
DOI: 10.1097/00003246-199902000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine and amrinone on contractility and cyclic adenosine monophosphate generation of tumor necrosis factor alpha-exposed cardiac myocytes

Abstract: Our data suggest that TNF-alpha induces a defect in beta-adrenergic signal transduction and catecholamine-stimulated contractility in neonatal rat cardiac myocytes. In addition, TNF-alpha augments the inotropic response of myocardial tissue to phosphodiesterase inhibitors through a mechanism independent of cyclic AMP generation. Phosphodiesterase inhibitors such as amrinone may be found to exert significant inotropic effects in catecholamine-refractory septic shock with myocardial depression and other conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Coincubation of TNF-␣, IL-1␤, synergistic combinations of the two, or human septic serum with competitive inhibitors of NO synthase (NOS) attenuates or prevents depressant responses in isolated cardiac myocytes. TNF-␣ also blunts generation of cAMP and contractile response to catecholamine stimulation in these myocytes (18). This observation is congruent with evidence of sepsis-associated cardiovascular resistance to adrenergic stimulation noted in a variety of clinical and experimental studies of sepsis and septic shock (15,16,20,26,33).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Coincubation of TNF-␣, IL-1␤, synergistic combinations of the two, or human septic serum with competitive inhibitors of NO synthase (NOS) attenuates or prevents depressant responses in isolated cardiac myocytes. TNF-␣ also blunts generation of cAMP and contractile response to catecholamine stimulation in these myocytes (18). This observation is congruent with evidence of sepsis-associated cardiovascular resistance to adrenergic stimulation noted in a variety of clinical and experimental studies of sepsis and septic shock (15,16,20,26,33).…”
supporting
confidence: 80%
“…We have previously demonstrated that TNF-␣ exposure results in an early effect of attenuation of ␤-adrenoreceptor-mediated increases in myocyte contractility and cAMP generation (18). Bick et al (3) have also shown that short-term neonatal rat cardiac myocyte exposure to TNF-␣ results in blunted contractility and cAMP response to isoproterenol but that responses to forskolin are preserved.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In vitro tests of PDE inhibitors on mouse and human macrophages showed inhibition of TNF-␣ and interleukin production (36,37). The cytokines are known to be responsible for cardiac depression and capillary leak syndrome during septicaemia and after cardiopulmonary bypass (7,10). In adult patients after cardiopulmonary bypass and during septic shock, enoximone reduced endotoxin and TNF-␣ levels compared with dobutamine-treated patients (30,38).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that this also occurs acutely after exposure to cytokines (Figure 2). In isolated mammalian myocytes, within minutes of exposure to cytokines such as TNF-␣, IL-1␤, and IL-6, there is an inhibition of catecholamine-stimulated contractility, 71,75 cAMP generation, 71 and I Ca augmentation. 75,76 The mechanism for this defect in ␤-AR signal transduction is not clear, although one study 76 suggested a mechanism unrelated to alterations in ␤-AR binding, adenylyl cyclase (AC) activity, or cAMP.…”
Section: Other Mechanismsmentioning
confidence: 99%